Is Adjuvant Chemotherapy Beneficial to All Patients With pT3N0M0 Stage Gastric Cancer? - Huang, Jiao-Bao; Lu, Jun; Wu, Dong; Xu, Bin-bin; Xue, Zhen; Lin, Guo-Sheng; Zheng, Hua-Long; Shen, Li-li; Lin, Jia; Xie, Jian-Wei; Wang, Jia-Bin; Lin, Jian-Xian; et al. (Frontiers in Oncology, 2021)
Background The efficacy and benefits of adjuvant chemotherapy (AC) for patients with gastric cancer pT3N0M0 remain controversial. Methods We prospectively collected and retrospectively analyzed 235 patients with pT3N0M0 gastric cancer who underwent radical resection between February 2010 and January 2016. Patients were divided into two groups: the surgery-alone (SA) group (n = 82) and the AC group (n = 153). We analyzed the effects of AC on the overall survival (OS) and recurrence-free survival (RFS), and the relationship between the number of chemotherapy cycles (CC) and recurrence rate (RR). Results The 5-year OS and RFS of the participants were 80.9% and 87.7%, respectively, and those in the AC group were significantly higher than those in the SA group (86.9% vs. 69.5%, p = 0.003). The RFS of the AC and SA groups were 88.9% and 85.4%, respectively; the difference was not statistically significant (p = 0.35). The independent risk factors affecting the OS were perineural invasion-positive (PNI+) (HR = 2.64, 95%CI: 1.45–4.82, p = 0.003) and age ≥ 65 years (HR = 2.58, 95%CI: 1.39–4.8, p = 0.003). The independent risk factor affecting the RFS was also PNI+ (HR3.11; 95%CI: 1.48–6.54, p = 0.003). Stratified analysis revealed that postoperative AC can significantly improve the OS of PNI+ patients (AC group versus SA group: 84.1% vs. 45.5%, p = 0.001) and RFS (86.4% vs. 63.6%, p = 0.017). However, perineural invasion negative (PNI-) patients did not show the same results (p = 0.13 and p = 0.48, respectively). According to the number of CC, divided into CC < 3 groups and CC ≥ 3 groups, the cumulative RR in the CC ≥ 3 group of patients with PNI+ was significantly lower than that of the CC < 3 group (7.4% vs. 28.2%, p = 0.037). Conclusion For pT3N0M0 gastric cancer patients with PNI+, at least three cycles of postoperative AC can significantly reduce the overall RR. This finding should be verified by using large external sample data.